THE IMPACT OF MINIMUM WAGE, GRDP, INFLATION, AND EDUCATION ON UNEMPLOYMENT RATE IN LAMPUNG PROVINCE - I Dewa Gede Sukadwipa (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study investigates the impact of regional minimum wages (UMK) on the open unemployment rate (TPT) in Lampung Province from 2017 to 2023. Employing Panel EGLS (Random Effects) modeling using data from 15 regencies/cities, the study incorporates Gross Regional Domestic Product (GRDP), current inflation (INF), lagged inflation (INF-1), and average years of schooling (RLS) as control variables. The findings show that MSEs do not significantly influence TPT, while PDRB and RLS positively affect unemployment, and lagged inflation negatively affects unemployment. The results imply structural mismatches in the labor market and highlight the need for synchronized education and labor policies to enhance employment in Lampung.